Frequency of Asymptomatic Spontaneous Bacterial Peritonitis in Outdoor Patients with Liver Cirrhosis (Medical Forum Monthly, 2024)
Objective: Investigate the incidence of asymptomatic spontaneous bacterial peritonitis in patients with liver cirrhosis.Study Design: Prospective study.Place and Duration of Study: This study was conducted at the Gastroenterology Department of Bakhtawar Amin Hospital and Nishtar Hospital Multan from May 2018 to May 2019.Materials and Methods: Eighty six patients of liver cirrhosis were included in the study. Main variables were serum albumin, prothrombin time, ascitic fluid protein, serum bilirubin, child class B, child class C. SPSS version 23 was used for data analysis. Test of significance student t-test and chi square test were applied. P value ≤0.05 was taken a s significant.Results: S. Albumin, PT (s), Ascitic Fluid Proteins, S. Bilirubin, TLC, ESR and CRP of SBP negative patients was 29.55±2.95 (g/dL), 28.97±1.25, 1.87±0.22 (g/dL), 54.21±2.15mMol/L, 11.91±2.21 (x109 /L), 34.37±2.18 (mm/h) and 56.47±2.33 (mg/ L), respectively. Child class C and child class B was observed as 64.5% and 31.6%, respectively.Conclusion: High frequency of spontaneous bacterial peritonitis is associated with liver cirrhosis; early diagnostic parenthesis should be performed in all outdoor patients for detection of silent cases of peritonitis. Antibiotic prophylaxis reduces the incidence of SBP.